Sentiment Analysis on Trans-nationalization of Digital Activism: The Case of #MilkTeaAlliance - Permana, Aditya; Christianto, Regina (ARISTO, 2025)
Milk tea, a beloved beverage in Asia, has evolved into a symbol uniting pro-democracy activist. The hashtag #MilkTeaAlliance, propagated on Twitter (now â€œXâ€), emerged as a potent force for trans-national advocacy, uniting individuals online and onsite in the fight against authoritarianism across regions, including Hong Kong, Taiwan, Thailand, and Myanmar. This study delves into the role of Twitter in raising awareness about authoritarian oppression on a trans-national scale, elucidating the movementâ€™s patterns on the platform. To comprehend the process of trans-nationalization, the study explores how a â€˜scale shiftâ€™ from national to international is facilitated through Trans-national Advocacy Networks. The findings underscore the pivotal role of Twitterâ€™s openness as a key platform, coupled with the movementâ€™s strategy of disseminating factual information and garnering support, which contributed to its remarkable success in capturing attention.